2018
DOI: 10.1051/mattech/2018050
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the surface quality, density and dimensional correctness in selective laser melting of the Ti-13Zr-13Nb alloy

Abstract: Selective laser melting is widely used for custom-designed elements. Successful manufacturing depends on laser treatment parameters and material features. This research aimed to determine the effects of laser power, scan time and hatch distance on surface quality, relative density and dimensional precision for cuboids made of the Ti-13Zr-13Nb alloy. The influence of energy density, energy flux and pre-heating was seen to be decisive to different degrees for the quality of the final specimen. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The porosity and pore size are dependent on the kind of space holder and the ratio of the titanium biomaterial to a space holder. As the space holders, NaCl [80][81][82], sugar crystals [83][84][85], polypropylene carbonate [86], magnesium powder [87,88], carbonates [89][90][91][92], carbamide [93,94], and Mo wire [95] were used. The titanium hydride, which could decompose at elevated temperature, was also applied in powder metallurgy.…”
Section: Pore Shapementioning
confidence: 99%
See 1 more Smart Citation
“…The porosity and pore size are dependent on the kind of space holder and the ratio of the titanium biomaterial to a space holder. As the space holders, NaCl [80][81][82], sugar crystals [83][84][85], polypropylene carbonate [86], magnesium powder [87,88], carbonates [89][90][91][92], carbamide [93,94], and Mo wire [95] were used. The titanium hydride, which could decompose at elevated temperature, was also applied in powder metallurgy.…”
Section: Pore Shapementioning
confidence: 99%
“…In [83], the 1:1 Ti/sugar ratio led to the porosity of about 72% with a pore diameter of 0.8-1.0 mm equaling the diameter of sugar crystals. The powder metallurgy without space holders was seldom attempted [91,98,99].…”
Section: Pore Shapementioning
confidence: 99%
“…The authors revealed slight anisotropy in the powder layer melting direction (horizontal) and in the layer addition direction (vertical); the reason for the abovenamed anisotropy being the presence of twin boundaries in the structure in the vertical direction and the arrangement of beta grains in the privileged direction in the longitudinal position. The structure of test specimens revealed the predominant presence of phase β and acicular martensite α' [6,[27][28][29]…”
Section: Alloy Ti13nb13zrmentioning
confidence: 99%
“…Recently, titanium materials have been developed as powders for the AM process. There are several reports showing that frameworks and clasps of removable dentures and fixed dentures can be produced by AM using titanium materials [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Moreover, Iseri et al [ 17 ] reported increased bonding strength of ceramics to titanium alloy specimens molded by AM compared to those of titanium alloy specimens prepared by casting.…”
Section: Introductionmentioning
confidence: 99%